PENGARUH KEPRIBADIAN, ORIENTASI KERJA, DAN PENEMPATAN TERHADAP KINERJA PEGAWAI - Sri langgeng Ratnasari; Mutia Septiani (Program Sarjana Manajemen Universitas Internasional Batam, 2020)
Employee performance is one of the things that is very interesting to develop, because employee performance is crucial in determining the performance of partnerships. The purpose of this study was to analyze the effect on employee performance, encourage work on employee performance, placement on employee performance, and personality, encourage work, and placement on employee performance. This research uses quantitative methods. The population of this research is 50 employees of PT. Asuransi Kredit Indonesia Cabang Batam. The research sample of 50 employees, with census sampling technique. The analysis technique uses multiple linear regression. The results of this study indicate that there is no significant difference in employee performance, work planning is significant on employee performance, and placement is not significant on employee performance, and competence, encouraging work, and significant placement on employee performance.